Odonata of the Kampar Peninsula: the first systematic survey of Odonata in Peat Swamp Forest in Sumatra - Dow, Rory A.; Gesriantuti, Novia; Iqbal, Muhammad; Ingdyah, Pungki Lupiyan; Periera, John F.; Zulya, Shinta O.; Sanders, Bradford M. (Zootaxa, 2025)
Sumatra, the second largest island in Sundaland, has been poorly studied for Odonata. Sumatra has ca. 72,300 km2 of peatlands which, prior to human alteration, were almost entirely covered by Peat Swamp Forest (PSF); Riau Province has the largest peatlands on the island. Less than 20% of Sumatra’s peatlands remain as PSF (pristine or degraded). PSF is known to provide habitat for specialised and/or threatened plant and animal species, including Odonata, but has received little sampling effort. No study on Odonata of any PSF area in Sumatra has been reported until now. The Kampar Peninsula in Riau Province has the largest remaining PSF (3,445.73 km2) in Sumatra, with 1,300.95 km2 specifically managed by the Restorasi Ekosistem Riau (RER) programme with the aim of protecting and restoring the degraded PSF at the core of the peninsula. In early 2020 the first author, together with Universitas Muhammadiyah Riau, commenced surveys of Odonata in the Kampar Peninsula, funded and facilitated by RER. After a long pause due to the global Covid-19 pandemic, surveys resumed in 2023. All surveys were conducted under research permits issued by the Indonesian National Research and Innovation Agency. The results of the Odonata surveys in the Kampar Peninsula are presented here. Surveys were conducted in January 2020, February 2023, May/June 2023 and September/October 2023, the spacing of and weather conditions during the surveys are discussed. Ninety-seven individual sites where specimens were collected are listed, grouped into 19 general areas. One hundred species and subspecies recorded during the surveys are listed with notes on habitat and in some cases other remarks. Taxonomic notes and remarks are given for some of the taxa recorded (Podolestes buwaldai Lieftinck, 1940, Copera vittata (Selys, 1863), Mortonagrion sp. cf. aborense (Laidlaw, 1914), M. megabinluyog Dow & Choong, 2015, M. sp. cf. forficulatum Lieftinck, 1953, Teinobasis ruficollis (Selys, 1877), T. sp. cf. suavis Lieftinck, 1953, Gynacantha dohrni Krüger, 1899 and G. maclachlani Krüger, 1899 (under the first name), Heliaeschna crassa Krüger, 1899 and H. idae (Brauer, 1865) (under the first name). In particular three forms of penile organ found in the M. aborense complex in Sumatra are discussed and illustrated with sketches; the structure of the female prothorax in T. ruficollis is discussed; the taxonomic history, status of type material, and diagnostic characters of G. dohrni and G. maclachlani are discussed in detail and illustrated with stacking images of the male anal appendages of type material of both species. Ninety-four of the taxa recorded are identified to a named species or subspecies, five are only identified with certainty to genus level, pending further taxonomic work and collection of more samples, and one taxon is identified as an unnamed but already known species. Of the distinct taxa recorded, 42 are from the Zygoptera and 58 from the Anisoptera. Most sampled habitats can be classified as either lowland swamp forest or open and disturbed; typically for both classes of habitat, the majority of species recorded are from the Coenagrionidae and Libellulidae. Eighty-nine of the 94 taxa identified to a named species/subspecies have also been recorded in Peninsular Malaysia and/or Singapore. At least 38 of the taxa recorded represent first published records for either Indonesia (five species: Amphicnemis bebar Dow, Choong & Ng, 2010, Amphicnemis hoisen Dow, Choong & Ng, 2010, Amphicnemis reri Dow, Gesriantuti & Lupiyaningdyah, 2025, M. megabinluyog and Chalybeothemis chini Dow, Choong & Orr, 2007), Sumatra including satellite islands (two taxa), mainland Sumatra (six taxa) or Riau Province (25 taxa); these first records are discussed. With these results 271 species of Odonata are known from Sumatra and 126 from Riau Province. Of the 100 distinct taxa recorded in the surveys in the Kampar Peninsula we regard 49 as forest-dependent (requiring the presence of forest for their survival) and 14 as specialists of low pH waters. A discussion of the species found in natural forest, planted forest and open habitats is included. Fifteen of the species recorded currently have IUCN Red List assessments other than Least Concern (four Data Deficient, one Endangered, three Vulnerable and seven Near Threatened. One species, A. reri, has not yet been assessed but would likely fall in one of the threatened categories with the data available. Fifteen percent is a high proportion of non-Least Concern species for a sample of Odonata in a relatively small area but fairly typical for low pH water habitats in Sundaland; all but one of the species regarded as low pH specialists have non-Least Concern Red List assessments. A comparison of the odonate fauna of the Kampar Peninsula with that of PSF areas in Borneo and Peninsular Malaysia is made and odonate diversity at low pH waters in Sundaland is discussed.